ANALYSIS OF THE ROLE OF JOB SATISFACTION AS A MEDIATING COMPENSATION AND WORK ENVIRONMENT RELATIONSHIPS TO EMPLOYEE PERFORMANCE - Djoko Soelistya; Riduansah Riduansah; Hadi Ismanto (SEAN Institute, 2023)
Aim from study this is for knowing is there influence environment work and compensation to performance employee with satisfaction work as variable between at PT Sinar Sun Sun Motorcycle. Study this use test validity, test reliability, test regression linear double, and test analysis track with help program SPSS version 20. Sample which taken as much 110 respondent. Study use approach quantitative with method technique purposive sampling. Data collection was carried out with deployment questionnaire use scale Likert for measure every statement. Results study show that there is influence positive and significant _ in a manner separated Among environment work and compensation to performance employee in a manner direct. Whereas mark significance influence environment work and compensation through satisfaction work no more big from influence direct.